2013
DOI: 10.1371/journal.pone.0082844
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Flowering Related microRNAs in Common Wild Rice (Oryza rufipogon Griff.)

Abstract: BackgroundMicroRNAs (miRNAs) is a class of non-coding RNAs involved in post- transcriptional control of gene expression, via degradation and/or translational inhibition. Six-hundred sixty-one rice miRNAs are known that are important in plant development. However, flowering-related miRNAs have not been characterized in Oryza rufipogon Griff. It was approved by supervision department of Guangdong wild rice protection. We analyzed flowering-related miRNAs in O. rufipogon using high-throughput sequencing (deep seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 63 publications
(73 reference statements)
6
36
0
Order By: Relevance
“…Similar to other reports of deep sequencing of microRNAs in rice, the expression of conserved miRNA families was significantly higher than that of non-conserved miRNAs (Sunkar et al , 2008; Zhu et al , 2008; Li et al , 2011; Chen et al , 2013). MicroRNA166 was most abundantly present across the 16 rice libraries sequenced in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other reports of deep sequencing of microRNAs in rice, the expression of conserved miRNA families was significantly higher than that of non-conserved miRNAs (Sunkar et al , 2008; Zhu et al , 2008; Li et al , 2011; Chen et al , 2013). MicroRNA166 was most abundantly present across the 16 rice libraries sequenced in this study.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, the cleaveage sites could be diverse. For instance, the cleavage site in the AK106348 mRNA by osa-miR3981-5p located at 13 th to 14 th [39]; Os09g03610 was cleaved by osa-miR819 at 12 th to 13 th and 16 th to 17 th [23]. Furthermore, osa-miR1848 could regulate OsCYP51G3 transcript, wherea the 5’ RLM-RACE test revealed that OsCYP51G3 mRNA was cleaved downstream of the osa-miR1848/OsCYP51G3 mRNA complementary site [40].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Oryza coarctata grows normally in saline water, and 338 known miRNAs and 95 novel miRNAs were found to respond to salt stress [22]. In 2013, we also identified flowering-related miRNAs in CWR [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that miRNAs regulate the expression of target genes through target mRNA degradation or translation inhibition [1][2][3]. As an important mechanism of post-transcriptional regulation, miRNAs could regulate genes involved in many developmental processes, such as flowering time, leaf development, auxin signaling and organ polarity [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 95%